Efeito do treinamento resistido na função autônomica cardíaca, nos parâmetros bioquímicos e antropométricos de pessoas vivendo com HIV/AIDS - Medeiros, Jason Azevedo de (2014)
Introduction: The emergence of High Active Antiretroviral Therapy (HAART) increase the life expectancy of the persons living with HIV/AIDS (PLHIV), therefore the prolonged use cause metabolic implications and influences on body fat distribution and increase the cardiovascular diseases prevalence. Aims: Evaluate the effect of resistance training on heart rate variability, biochemical parameters and somatotype on PLHIV. Methods: Participated this study seven sedentary men, with age above 25 years old, living with HIV/AIDS, under HAART use. Were submitted a 16 week intervention with resistance training. Evaluated the heart rate variability, biochemical parameters and somatotype, before, after 8 weeks and 16 weeks, all in paired form. It was found the data normality by Shapiro-Wilk test and conducted the Anova one way combined with Tukey post hoc to samples in each evaluate moment, adopting significance level p<0,05. Also were calculated percentage change deltas. For somatotype was used the somatotype spatial distance (DES), obeying the significance value DES≥1. Results: Was found significance differences only in variable final heart rate delta 60s (p=0,01), however, is not showed changes on heart rate variability, biochemical parameters and somatotype components. Conclusion: 16 weeks of resistance training showed improvement on heart rate recovery after submaximal effort and, despite is not enough to produce significance differences on biochemical parameters and somatotype components, could be realize improvement on average value of fasting glucose and lipid profile, as well as reducing the endomorphic component